OPTIMASI TABLET FLOATING TEOFILIN MENGGUNAKAN METODE DESAIN FAKTORIAL - agus siswanto; Indri Hapsari; yusni ulfiani zulaikha; eva rosmawati (Universitas Muhammadiyah Prof. DR. HAMKA, 2016)
ABSTRACTTheophylline is a drug used in the management of asthma. It has relatively short half-life and narrow therapeutic index with 5-20 μg/mL serum concentration. Thus, Floating tablet formulations that can increase the bioavailability of the drug. The aims of this study were to determine the effect of the excipient (HPMC K4M CR and NaHCO3) to the quality of tablets and determine the optimum formula of theophylline floating tablet. A 22 randomized factorial design was used in development of theophylline floating tablet with HPMC K4M CR (A) and NaHCO3 (B) as independent variables.The flowability of mass tablet, floating character, and dissolution profile were chosen as dependent variables.The results showed that NaHCO3 was the most important factor on increasing flowability of mass tablet. HPMC K4M CR was the dominant factor in lowering the Flag time, improving integrity of the tablet, and decreasing the release of drug. The composition of HPMC K4M CR 40.00 mg and NaHCO3 35.39 mg produced the optimum formula of theophylline floating tablet with desirability value of 0.978.